Soils and Fertlilizers for Master Gardeners: Soil Fertility - Amy L. Shober (EDIS)
Revised! SL-267, a 2-page fact sheet by Amy L. Shober, explains the chemical properties of the soil that influence soil fertility and discusses the fertility of Florida’s soils. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Includes references. Published by the UF Department of Soil and Water Science, January 2009.